ANALISIS EFEKTIVITAS DAN EFISIENSI PENGGUNAAN FAKTOR PRODUKSI MODAL PADA USAHA PETERNAKAN AYAM BANGKOK DI KOTA TIMIKA (STUDI KASUS PETERNAKAN AYAM BANGKOK BAPAK ROBI DI SP 1) - Sarlita Ode; Indriani Ar, Tri Apriyono (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research aims to determine the effectiveness and efficiency of the use of capital production factors in Mr. Robi's Bangkok chicken farm. The research method employed is descriptive. To analyze the effectiveness of capital production factor utilization in Mr. Robi's Bangkok chicken farm, effectiveness and efficiency analyses were conducted. The research results indicate that the utilization of capital production factors has a percentage of 90.8%, indicating effective capital usage. Meanwhile, the efficiency analysis results of capital production factor utilization in Mr. Robi's Bangkok chicken farm are below 60, indicating highly efficient utilization of production factors in Mr. Robi's Bangkok chicken farm